2008
DOI: 10.1177/1352458508094644
|View full text |Cite
|
Sign up to set email alerts
|

3D MPRAGE improves classification of cortical lesions in multiple sclerosis

Abstract: Background-Gray matter lesions are known to be common in multiple sclerosis (MS), and are suspected to play an important role in disease progression and clinical disability. A combination of MRI techniques, double-inversion recovery (DIR) and phase-sensitive inversion recovery (PSIR), has been used for detection and classification of cortical lesions. We now demonstrate that highresolution three-dimensional (3D) magnetization-prepared rapid acquisition with gradient echo (MPRAGE) improves the classification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 19 publications
4
88
0
Order By: Relevance
“…The detected cortical lesion load is comparable with the bulk of cortical lesions assessed by specialized MR imaging methods developed for sensitive cortical lesion delineation. 13,15,16,18,29 While it has been reported that cortical lesions are more conspicuous on 3D double inversion recovery compared with 3D-FLAIR images, 13,17 the former is not yet widely available on clinical scanners. FLAIR hyperintensities might represent lesions, perivenular spaces, or CSFrelated flow artifacts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The detected cortical lesion load is comparable with the bulk of cortical lesions assessed by specialized MR imaging methods developed for sensitive cortical lesion delineation. 13,15,16,18,29 While it has been reported that cortical lesions are more conspicuous on 3D double inversion recovery compared with 3D-FLAIR images, 13,17 the former is not yet widely available on clinical scanners. FLAIR hyperintensities might represent lesions, perivenular spaces, or CSFrelated flow artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,10,12 While ultra-high-field MR imaging allowed depiction of subpial lesions, 18,19 previous MR imaging studies at field strengths Ͻ4T were similarly to our method unable to visualize them. [14][15][16][17]34 The multiplanar display of our isotropic resolution IR-SPGR images allowed precise anatomic lesion classification in relation to the gray matterϪwhite matter junction and cortical folding patterns. We believe this is a critical step in assigning lesions to their proper subtype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DIR improves the sensitivity of MRI to detect cortical lesions in vivo, [62][63][64][65] although it has shown low interobserver concordance, particularly for the detection of pure intracortical lesions, thereby limiting its value in clinical practice. 63 Other sequences, such as phase-sensitive inversion recovery (PSIR) and highresolution 3D magnetization-prepared rapid acquisition with gradient echo (MPRAGE), improve intracortical lesion classification, 62,63,[67][68][69] especially at high magnetic field strengths.…”
Section: Differential Diagnosis Via Lesion Distributionmentioning
confidence: 99%